(untitled) (Journal of Oriental Studies, 2016)
This paper aims at conducting studies on contrastive linguistics of Japanese and Kazakh and interlanguage studies of Kazakh learners’ Japanese. The paper indicates research themes of contrastive analysis of the languages from the view point of grammar (case and auxiliary verb) and pragmatics (refusal , request and apologу).